Uncoupling of natural IgE production and CD23 surface expression levels. - Weicheng Ren; Kristina Lagerstedt; Ola Grimsholm; Anna Stern; Jia-Bin Sun; Yu Fang; Zou Xiang; Inga-Lill Mårtensson (PLoS ONE, 2013)
CD23, the low affinity receptor for immunoglobulin E (IgE), has been proposed to play a critical role in the regulation of IgE production, based on altered IgE levels in CD23-deficient mice and transgenic mouse models, as well as in mouse strains with mutations in the CD23 gene, e.g. 129 substrains. Here, we have investigated a mouse line termed LxT1 that expresses reduced CD23 surface levels on B cells, and its influence on natural IgE production. Extensive phenotypic analysis showed that CD23 surface expression was reduced in LxT1 compared to the control, without affecting B cell development in general. This CD23(low) surface level in LxT1 mice is not as a result of reduced CD23 mRNA expression levels or intracellular accumulation, but linked to a recessive locus, a 129-derived region spanning 28 Mb on chromosome 8, which includes the CD23 gene. Sequence analysis confirmed five mutations within the CD23 coding region in LxT1 mice, the same as those present in New Zealand Black (NZB) and 129 mice. However, this CD23(low) phenotype was not observed in all 129 substrains despite carrying these same CD23 mutations in the coding region. Moreover, serum IgE levels in LxT1 mice are as low as those in the C57BL/6 (B6) strain, and much lower than those in 129 substrains. These data indicate that the CD23 surface level and serum IgE level are uncoupled and that neither is directly regulated by the mutations within the CD23 coding region. This study suggests that caution should be taken when interpreting the immunological data derived from mice with different genetic background, especially if the gene of interest is thought to influence CD23 surface expression or serum IgE level.